Reducing the Intergenerational Gap between Senior and Younger Employees through OD Interventions on Communication, Leadership, Work Values and Knowledge Management: An Action Research at a Thai Workplace - Srisuwan, Nid; Rucktum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The perception of an intergenerational gap between the senior and younger employees spawns hurdles and difficulties in many workplaces, including an air cargo company based in Bangkok, Thailand. According to the initial assessment results, it was most apparent in the areas of communication, leadership, work values (WVs), and knowledge management (KM). This study reviewed literature on intergenerational gap and the identified issues, designed organization development interventions (ODIs), and implemented them to address the problems. The study was carried out among 40 full-time staff, representing several departments and two major generations at the company. The ODIs took the form of introduction to relevant OD workshops, activities, discussions using appreciative inquiry process. Participants’ attitudes and opinions were measured in the five areas before and after the ODIs using quantitative and qualitative designs. Following the ODIs, paired samples t-tests and focus group results showed that the perceived intergenerational gap and the four key issues were significantly reduced. MLR post-ODI demonstrated that communication had a significant relationship with intergenerational gap. However, other variables showed no significant relationship. This may be due to the confounding factors in the quasi-experiment or limited sample size. The study suggested that companies who employed several generations at workplaces could use the ODI in this study as a starting point for generation gap bridging discussion and improvement in terms of communication, leadership styles, WVs, and KM. It also serves as a basis for revisiting intergenerational debate from the Thai cultural context, which differ from the context in which most generational theories originated. Future studies could focus on validating the models that emerged from that debate.